Incredibly Committed? Assessing Regulatory Agency Financial Autonomy in Brazil From a Critical Perspective - Bruno Queiroz Cunha; Mauro Santos Silva (Journal of Politics in Latin America)
Despite the expansion of the regulatory agency model in Brazil since 1996, specialized literature has raised concerns that the autonomy of the country's regulators has been persistently undermined. Based on a novel 22-year budget dataset, this study challenges the dominant thinking, as it points to a process of continuous institutional embedding. Nevertheless, this process has been endangered by fiscal austerity since 2016. The article contributes to the literature by presenting new ways in which organizational de facto autonomy can develop in state-dependent market economies. Moreover, it provides political economy insights into the legitimacy acquired by regulatory agencies across the political spectrum in Latin America.